Production of N-acetylglucosamine from Semi Purified Chitinase of Mucor circinelloides that Immobilized by using Agar - Lucia Crysanthy Soedirga; Hardoko Hardoko; Natasha Vania Widianto (Universitas Gadjah Mada, 2019)
Hydrolysis of chitin into N-acetylglucosamine (NAG) can be done enzymatically by using chitinase enzyme that obtained from the fermentation with chitinolytic molds. Mucor circinelloides is one example of chitinolytic mold that can produce semi purified chitinase enzyme during the fermentation of chitin from black tiger shrimp (Penaeus monodon) shell. The semi purified chitinase enzyme that obtained in this research will be immobilized into the agar polymer to the extent of its stability during NAG production. This research was aimed to investigated the best concentration of agar (3,4,5, and 6%) and the best amount of added enzyme (0.2; 0.4; 0.6; 0.8; and 1 mL) toward the production of NAG. The result showed 0.6 ml of semi purified chitinase that immobilized into 3% of agar can produced NAG within the concentration 1111.667 ppm. Moreover, this enzyme considerably stable before and after immobilization within the value of 4.78 U/mL.